PENGELOLAAN SARANA PRASARANA TERHADAP SEMANGAT BELAJAR SISWA DALAM PEMBELAJARAN PAI - elvi, Elvi Khairiah; Safriadi; Sari Pitri (FITRAH: International Islamic Education Journal, 2023)
This research aims to understand how learning facilities are managed, especially in PAI learning, which includes the planning, procurement and maintenance processes. The research method applied is qualitative with an interpretative descriptive approach. The data collection method involves three aspects, namely, observation, interviews and documentaries and drawing conclusions. The respondents in this research were school principals, infrastructure management staff and PAI subject teachers and the data sources used were primary data and secondary data. The results of this research show that in the management of facilities and infrastructure in PAI learning and seeing how the enthusiasm for learning created by teachers at SMPN 3 Banda Aceh is carried out according to process standards and management, there is good planning of infrastructure, procurement in accordance with prioritized priorities and maintenance, the role Teachers also create enthusiasm for learning through a neat, comfortable and peaceful classroom management process, using fun learning methods.